A Robust Estimate of Continental‐Scale Terrestrial Carbon Sinks Using GOSAT XCO2 Retrievals. Issue 6 (21st March 2023) - Zhang, Lingyu; Jiang, Fei; He, Wei; Wu, Mousong; Wang, Jun; Ju, Weimin; Wang, Hengmao; Zhang, Yongguang; Sitch, Stephen; Walker, Anthony P.; Yue, Xu; Feng, Shuzhuang; et al.
Abstract: Satellite XCO2 retrievals could improve the estimates of surface carbon fluxes, but it remains unknown on what scales these estimates are robust. Here, we use the time‐dependent Bayesian synthesis top‐down method and prior net ecosystem exchanges (NEEs) from 12 terrestrial biosphere models (TBMs) to infer the monthly carbon fluxes of 51 land regions with constraints by GOSAT XCO2 retrievals. We find that the uncertainty (standard deviation of 12 TBMs) reduction rates (uncertainty reduction rate (URR)) decrease significantly at decreasing spatial scales. On the continental‐scale, the mean URR is about 57%, and the annual and seasonal cycle estimates of NEE are rather robust. The evaluation shows that the posterior CO2 concentrations are significantly improved at the continental scale. Our study suggests that the GOSAT XCO2 can only promise a robust continental‐scale NEE estimate, and improving the XCO2 accuracy is an effective way to achieve robust estimates on smaller scales under current spatial coverage. Plain Language Summary: Remotesensing‐based CO2 measurement can improve the estimates of surface carbon fluxes due to its relatively well global coverage, but it remains unknown on what spatial scales the satellite observation could provide a robust estimate. Here, net ecosystem exchanges (NEEs) from 12 terrestrial biosphere models (TBMs) of 51 land regions for the period of 2011–2014 are constrained using GOSAT XCO2 retrievals, and the uncertainty (standard deviation of 12 TBMs) reduction rates (uncertainty reduction rate (URR)) at different spatial scales are analyzed. We find that (a) from the whole globe to the mean of 51 regions, the URR decreases from 95% to 16%. (b) On the continental‐scale, the mean URR is about 57%, and the annual NEEs in Asia, N. America, Europe, S. America, Africa, and Australia are estimated to be −2.07 ± 0.25, −0.85 ± 0.09, −0.76 ± 0.21, −0.36 ± 0.17, −0.36 ± 0.30, and −0.15 ± 0.12 PgC yr −1, respectively. Our study suggests that the GOSAT XCO2 can only promise a robust continental‐scale NEE estimate, and improving the XCO2 accuracy is an effective way to achieve robust estimates on smaller scales under current satellite observing capacity. Key Points: Terrestrial carbon sinks estimated based on GOSAT XCO2 and net ecosystem exchanges (NEE) from 12 terrestrial biosphere models using atmospheric inverse method The uncertainty reduction rates decrease significantly at decreasing spatial scales The GOSAT XCO2 can only promise a robust continental‐scale NEE estimate